The Theory and Measurement of Work CommitmentThe Theory and Measurement of Work Commitment, by MorrowPaula C.. Greenwich, CT: JAI Press, 1993, 202 pp., $65.00, ISBN: 1-55938-572-3. - Rondeau, Kent V. (Academy of Management Review, 1994)
The article reviews the book ?The Theory and Measurement of Work Commitment,? by Paula C. Morrow.